Dog Days: James P. Cannon vs. Max Shachtman in the Communist League of America, 1931-1933 - Palmer, Bryan D. (Labour / Le Travail, 2003)
The article reviews the book, "Dog Days: James P. Cannon vs. Max Shachtman in the Communist League of America, 1931-1933," by Prometheus Research Library Staff.
Keywords: BOOKS -- Reviews; DOG Days: James P. Cannon vs. Max Shachtman in the Communist League of America 1931-1933 (Book); Nonfiction; POLITICAL participation